2022
DOI: 10.3389/fphar.2022.869482
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Monoacylglycerol Lipase Inhibition on Intestinal Permeability of Rats With Severe Acute Pancreatitis

Abstract: Background: Endocannabinoid 2-arachidonoylglycerol (2-AG) is an anti-nociceptive lipid that is inactivated through cellular uptake and subsequent catabolism by monoacylglycerol lipase (MAGL). In this study, we investigated the effects of MAGL inhibition on intestinal permeability and explored the possible mechanism.Methods: A rat model of severe acute pancreatitis (SAP) was established. Rats were divided into three groups according to treatment. We analyzed intestinal permeability to fluorescein isothiocyanate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In our previous research, numerous RNA-binding proteins (RBPs) were differentially expressed during SAP-induced intestinal injury and MAGL treatment, indicating they may have important functions. 5 Based on this, we evaluated intersections of DEGs with known RBPs in different cell clusters between CON and SAP groups, and between SAP and JZL184 groups. We observed numerous upregulated and downregulated RBP genes in cell clusters (such as C6 and C10) in our comparisons of different groups ( Figure S5A – D ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous research, numerous RNA-binding proteins (RBPs) were differentially expressed during SAP-induced intestinal injury and MAGL treatment, indicating they may have important functions. 5 Based on this, we evaluated intersections of DEGs with known RBPs in different cell clusters between CON and SAP groups, and between SAP and JZL184 groups. We observed numerous upregulated and downregulated RBP genes in cell clusters (such as C6 and C10) in our comparisons of different groups ( Figure S5A – D ).…”
Section: Resultsmentioning
confidence: 99%
“…The researchers involved in this study were blinded to specific details regarding the treatments administered to the animals. The protocol for establishing the SAP rat model and conducting the JZL184 treatment experiments followed the method outlined in our previous study (Wang et al, 2022). Twenty-four hours after the surgery, the SD rats were randomly divided into three groups: the Control group (CON), the SAP group (SAP), and the SAP group treated with JZL184 (JZL184).…”
Section: Animals and Ileal Tissue Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been implicated in several muscular dystrophies, including HNRNPDL-related muscular dystrophy with varying clinical and MRI phenotypes [ 94 , 95 ]. Additionally, HNRNPDL is found to be the most coexpressed RBP with alternative splicing events in severe acute pancreatitis [ 96 ]. Our findings further suggest the potential involvement of RBPs in the regulation of RNA editing in PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the latest meta-analysis [45 && ] showed that acupuncture was effective in reducing pain intensity, the time to relief, abdominal distention, and the time to relief of distension compared with routine treatment of acute pancreatitis pain. Two studies [47,48] noted that acupuncture reduced intestinal permeability and the local inflammatory response. Taken together there is now sufficient evidence to state that acupuncture reduces the need for opioids, reduces inflammation and promotes gastrointestinal motility.…”
Section: Acupuncture and Transcutaneous Electrical Nerve Stimulationmentioning
confidence: 99%